Chromosome 18 ring syndrome. Case report and review of the literature (Boletin Médico de Postgrado, 2020)
Chromosome 18 Ring Syndrome (18 [(r) 18]) is a chromosomal disorder that is included among the unbalanced structural anomalies in which chromosome 18 has a ring form which results from the simultaneous loss of both terminal segments of the short and long arms with the subsequent fusion of their ends forming a circular structure that microscopically resembles a ring, hence its nomenclature r (of the English ring, which means ring).18r Syndrome has an incidence of 1/40,000 live births; to date approximately 80-100 cases worldwide have been reported. There are only about nine reports of r(18) in mosaic, isolated or associated with other chromosomal alterations. We present a case of a pediatric patient with Chromosome 18 Ring Syndrome, evaluated and diagnosed in the Unidad de Genética Médica of the Universidad Centroccidental Lisandro Alvarado in Barquisimeto, Venezuela with the corresponding review of the literature.
Keywords: Chromosomes; humans; pair 18; ring chromosome 18; facial dysmorphia; genetic counseling